Tashwir Mujtama’ Mishra fi Majmuah al Qashidah “al Diwan al Awwal” li Hisyam al Jakh inda Nadzariyah Alan Swingewood - Amilatul Khoiriyah; Wildana Wargadinata; Faris Maturedy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study was to know the representation of Egyptian society in Hisyam Algakh poems “Ad- Diwaan Al-Awwal” based on the perspective of Alan swingewood's first literary work as social document at the time of the work's creation.This type of research is descriptive qualitative. The primary source of data used in the study are the three of Hisyam Algakh poems “Ad- Diwaan Al-Awwal” entitled ar-Risalah al-Akhirah, Masyhadu Ra’si Fi Miidan at-Tahrir dan at-Ta’syirah. The data collection techniques used by researchers in this study are reading, translation, and note-taking techniques. The data validation technique in this study consists of increasing diligence, triangulation, discussions with experts. The data analysis technique used in the study of the Miles Huberman model are reduction, presentation and drawing conclusions. The results of this study show representation of Egyptian society in the poetry collection “Ad- Diwan Al- Awaal” by Hisyam Algakh, there are 4 descriptions: a) a complaints against to the head of state that does not hear the sigh of its people; b) the misery of society resulting from authoritarian leadership; c) the hope of the Egyptian people; and d) nationalism conceived in the form of love for the fatherland and the Arabs.